Perlindungan Hukum Terhadap Hak-Hak Konsumen Terkait Tiket Pesawat Yang Dibatalkan Maskapai Penerbangan Masa Pandemi Covid-19 - Ferdiana Mailawati; Sri Wahyuni (KRTHA BHAYANGKARA, 2021)
Air transportation is one of the means of air transportation that is needed by someone who wants to travel between islands and even between countries with long enough distances that can be traveled in a relatively faster time when compared to other transportation. However, when consumers have ordered and paid for airline tickets with certain destinations according to their needs and needs, when the COVID-19 pandemic hit Indonesia and even almost all countries in the world experienced it, there were several policies carried out by the government of the Republic of Indonesia in order to prevent the transmission of the virus. This has an impact on aviation transportation. so that there are flight transportation schedules that have been cancelled. This study will answer the question of how the legal protection of consumer rights related to the cancellation. Normative juridical research method with a legal approach, namely regulations related to consumer and aviation protection that apply in Indonesia. The results of this study analyze the legal protection of consumer rights related to compensation when the flight ticket that has been ordered is canceled by the airline between the facts and the relevant regulations are appropriate.